The Brooklyn Health Map: Reflections on a Health Data Dashboard for Brooklyn, NY - Sheena Philogene (Code4Lib Journal, 2023)
Recent years have put a spotlight on the importance of searchers of all kinds being able to quickly and easily find relevant, timely, and useful health information. This article provides a general overview of the process used when creating the Brooklyn Health Map, an interactive Brooklyn-based health data dashboard that visualizes community health information at the census tract, zip code, and neighborhood levels. Built using HTML, CSS, Bootstrap, and JavaScript, the Brooklyn Health Map presents information in the form of interactive web maps, customizable graphs, and local level data summaries. This article also highlights the tools used to simplify the creation of various dynamic features of the dashboard.